A contribuição de Esther Lederberg (1922-2006) para o campo da microbiologia: um percurso feminino - Amado, Glaucy Cristina do Amaral (2022)
The study of bacteria as an organism capable of performing biochemical reactions and useful for research into the genetics of chromosomes began when scientists, in the early 1940s, began to use microorganisms that performed more efficiently after mutation. Initially, the fruit fly, the Neurospora fungus and corn were used. In this context, that our Esther Lederberg could start her scientific career, she was an intern/assistant of important researchers such as Bernard Dodge, Edward Tatum and George Beadle, worked in the research laboratory analyzing Neurospora mutants exposed to radiation and, by using the same method, separated mutants of E. coli, she was a researcher in the laboratory of her husband Joshua Lederberg, where she developed research related to bacterial sexual behavior. This thesis aims to demonstrate the major discoveries of scientist Esther Lederberg using the E. coli Bacteria strains K-12. As well as the difficulties to develop her work in a male environment. The research points out how the scientist discovered the lambda bacteriophage, fertility factor F, and transduction in bacterial conjugation using these mutant strains and reports how she invented the plate replication technique using a purse make-up material. And how the study of gene recombination in bacteria contributed to the new field of genetic biochemistry. To do so, we resorted to documentation composed of published articles of her authorship, collected data in biographical texts and the official Esther Lederberg Memorial website, and consulted photographic images, letters and obituaries written by colleagues, for contextualization we took as reference texts by historians of science